2022
DOI: 10.51791/njap.v49i1.3431
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance of normal local chicken x Isa brown in Nigeria

Abstract: Indigenous chickens have some peculiarity that enables them withstand harsh weather, resistance to diseases and adaptive mechanism to the environment. However, the indigenous chickens have some disadvantages arising from rearing mortality, slow growth rates, poor egg production and attains sexual maturity late. Such birds can be improved genetically through selective breeding. The study was aimed at accessing the growth performance of Isa Brown (exotic) x Normal Local chicken progenies in a humid tropical regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This characteristic is evident in the relatively consistent feed conversion values observed from week to week, reflecting their suboptimal feed utilization [12,15]. Other studies, such as [7,16], also reported similar irregularities in FCR during the pre-starter phase, primarily due to the behavior of the chickens at this developmental stage.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…This characteristic is evident in the relatively consistent feed conversion values observed from week to week, reflecting their suboptimal feed utilization [12,15]. Other studies, such as [7,16], also reported similar irregularities in FCR during the pre-starter phase, primarily due to the behavior of the chickens at this developmental stage.…”
Section: Resultsmentioning
confidence: 65%
“…It is essential to emphasize that variations in body mass growth performance are primarily influenced by genetic traits [6,8,11,13]. Furthermore, it is worth noting that environmental factors, as well as feed and maintenance management, did not significantly impact the differences in body mass performance [7,17]. This is attributed to the equalization of these three factors among all BS chickens in this research.…”
Section: Resultsmentioning
confidence: 81%